A decision paradox: benefit vs risk and trust vs distrust for online dating adoption vs non-adoption. Issue 1 (31st August 2020) - Chen, Qi; Yuan, Yufei; Feng, Yuqiang; Archer, Norm
Abstract : Purpose: Online dating services have been growing rapidly in recent years. However, adopting these services may involve high risk and trust issues among potential users toward both online dating services and the daters they introduce to users. The purpose of this paper is to investigate how perceived benefits vs risks, and trust vs distrust affect user adoption vs non-adoption intentions toward using this rather controversial information and communications technology in the context of online dating. Design/methodology/approach: Structural equation modeling was used to evaluate the research model using data from a survey of 451 single individuals. Findings: The results indicated that perceived benefits play more essential roles in adoption, while perceived risks affect non-adoption more. Individuals' trust in online dating service predicts a major portion of the variation in user benefit perceptions, while distrust in online dating service and in daters that users might select significantly influence perceived risks. Moreover, benefit and risk perceptions can mediate the impacts of trust and distrust on both adoption and non-adoption decisions. Originality/value: This study extends theories of decision-making in the use of controversial information technologies such as in the case of online dating. It investigates the coexistence of various trust and distrust beliefs as well as benefit and risk perceptions, and their different impacts on adoption and non-adoption in online dating services.